Inside man [videorecording (DVD)] - Lee, Spike; Washington, Denzel, 1954-; Owen, Clive; Foster, Jodie (Universal Pictures, 2006)
NYPD Detective Keith Frazier struggles to outsmart Dalton, a high-stakes bank robber who, along with a well-trained crew of accomplices, has seized control of a Wall Street bank. The robbers turn what initially looks like a hostage crisis into a personal crusade to expose some mysterious evil secrets. As the dangerous cat-and-mouse game unfolds, Madaline, a power broker with her own agenda, emerges and injects even more instability into an already volatile situation.